NATURAL ELONGATION OF SPHERICAL TOKAMAKS - Roberto, M.; Galvao, RMO (Int Atomic Energy Agency, 1992)
The variation of the elongation of axisymmetric plasma columns in vertical equilibrium magnetic fields is investigated as a function of the aspect ratio using the Solov'ev equilibrium model and the principle of virtual casing.